Honeypots for Windows - Grimes, Roger A. (Apress : Imprint: Apress, 2005)
Installing a honeypot inside your network as an early warning system can significantly improve your security. Currently, almost every book and resource about honeypots comes from a Unix background, which leaves Windows administrators still grasping for help. But Honeypots for Windows is a forensic journeyhelping you set up the physical layer, design your honeypot, and perform malware code analysis. You'll discover which Windows ports need to be open on your honeypot to fool those malicious hackers, and you'll learn about numerous open source tools imported from the Unix world. Install a honeypot on your DMZ or at home and watch the exploits roll in! Your honeypot will capture waves of automated exploits, and youll learn how to defend the computer assets under your control.